2012
DOI: 10.1371/journal.pone.0044413
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Reference microRNAs for Relative Quantification in Porcine Tissues

Abstract: Relative quantification is the strategy of choice for processing RT-qPCR data in microRNAs (miRNAs) expression studies. Normalisation of relative quantification data is performed by using reference genes. In livestock species, such as pigs, the determination of reference miRNAs and the optimal number of them has not been widely studied. In this study, the stability of ten miRNAs (Ssc-let-7a, Ssc-miR-103, Ssc-miR-17-3p, Hsa-miR-25, Hsa-miR-93, Ssc-miR-106a, Ssc-miR-191, Ssc-miR-16, Ssc-miR-26a and Ssc-miR-17-5p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(36 citation statements)
references
References 34 publications
2
34
0
Order By: Relevance
“…The obtained results on the stability of miRNA expression are in partial agreement with those of Timoneda et al (2012) who investigated the stability of ten miRNAs in various tissues and breeds of pig. It was observed that all investigated miRNAs were stable and the expression of selected miRNAs was Figure 2.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The obtained results on the stability of miRNA expression are in partial agreement with those of Timoneda et al (2012) who investigated the stability of ten miRNAs in various tissues and breeds of pig. It was observed that all investigated miRNAs were stable and the expression of selected miRNAs was Figure 2.…”
Section: Discussionsupporting
confidence: 87%
“…Furthermore, the miR-335 was included in the study despite the fact that in the previous study (Pawlina et al, 2015) we did not detect it in the liver miRNAome by NGS (Next Generation Sequencing) but as many as seven DEG were possible targets for this miRNA. The let-7a was also included in the experiment because it has been shown to be a good endogenous control in the porcine liver (Timoneda et al, 2012).…”
Section: Selection Of Mirnas By In Silico Mirtarbase Analysismentioning
confidence: 99%
“…According to sequence count, nine miRNAs highly expressed (Hsa-miR-200b-3p, Hsa-miR-200c-3p, Ssc-miR-126, Ssc-miR-126*, Ssc-miR-99a, Ssc-miR-532-5p, Ssc-miR-92a, Ssc-miR-26a and Bta-miR-193b, n>100) and four miRNAs lowly expressed (Ssc-miR-423-5p, Ssc-miR-29c, Ssc-miR-486 and Ssc-let-7f, n<100) in the kidney miRNAome were selected to measure their expression levels by RT-qPCR. Hsa-let-7a, Hsa-miR-25 and Hsa-miR-93 were used as reference miRNAs based on literature [50], [51]. Primers used were designed by Exiqon® (Denmark).…”
Section: Methodsmentioning
confidence: 99%
“…The amplification program comprised an initial step at 95°C for 10 min, followed by an annealing step and an elongation step for 1 min at 60°C. Porcine miR-17, miR-103, and miR-17 served as reference miRNAs (25).…”
Section: Methodsmentioning
confidence: 99%